1997
DOI: 10.1038/hdy.1997.175
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation within and between populations of Posidonia australis, a hydrophilous, clonal seagrass

Abstract: Allozyme diversity was surveyed at 15 loci across 22 populations of the hydrophilous seagrass Posidonia australis (Hook. f.). Substantial genetic variation was detected (HT = 0.311) with a high proportion of this variation partitioned between populations (GST = 0.623). The high value of GST is attributed to large geographical distances between many of the populations and several of the extreme north-western populations having fixed homozygous genotypes. Southwestern populations of P australis were the most var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Locus PaB6 and PaB8 did not amplify (consistently) well in samples from Port Stephens, and less stringent PCR conditions were required. These results suggest deeply divergent eastern and western lineages within P. australis, consistent with earlier allozyme results (Waycott et al 1997). Seven of the 10 loci amplified in P. sinuosa samples, six of which were polymorphic (Table 2).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Locus PaB6 and PaB8 did not amplify (consistently) well in samples from Port Stephens, and less stringent PCR conditions were required. These results suggest deeply divergent eastern and western lineages within P. australis, consistent with earlier allozyme results (Waycott et al 1997). Seven of the 10 loci amplified in P. sinuosa samples, six of which were polymorphic (Table 2).…”
supporting
confidence: 88%
“…f. is widespread along the Australian coastline, occurring from Shark Bay in northern Western Australia around the southern coast to Lake Macquarie in central New South Wales, and along the northern coast of Tasmania (Gobert et al 2006). Population differentiation at a broad geographic scale has been reported in P. australis, but these results were based on a low number of weakly polymorphic markers e.g., five polymorphic allozyme loci (Waycott et al 1997) and 28 Pa118/9R…”
mentioning
confidence: 94%
“…In addition, all genetic parameters were not significantly correlated with soil pH and longitude (Table 8). (Waycott et al, 1997). Many studies have shown that the average ratio of different genotypes (PD) and Simpson diversity index (D) of asexually reproduced plants are 0.62 (0.1-1.00) and 0.75 (0.13-1.00), respectively (Widén et al, 1994).…”
Section: Correlation Between the Genetic Diversity And Environmental mentioning
confidence: 99%
“…However, other studies of phylogeny based on a nuclear marker (rRNA-ITS) revealed a more ancient split between the Mediterranean and Australian taxa (>60 Myr BP). Based on this evidence, the Australian Posidonia species are probably the survival descendants after the separation of Australia from Antarctica during the Eocene (55.8 to 33.9 Myr BP) [7, 16], followed by a more recent divergence of the two recognized Australian complexes around 12 Myr ago [1]. In the northern hemisphere only P .…”
Section: Discussionmentioning
confidence: 99%